Kecemasan pada pasien COVID-19 - tiawati, Sulis (LPPM STIKES MUHAMMADIYAH GOMBONG, 2021)
Objective: To determine the effect of non-pharmacological therapy in reducing anxiety in COVID-19 patients.Method: The method used in this Literature review is to search for publication results between 2015-2020 through Google Scoolar and PubMed searches. The search results obtained using the Boolean method in the form of full text and pdf, then reviewed using the CASP (Critical Appraisal Skill Program), extracted then discussed and concluded.